Reproductions of Chinese Transnationalism: Ambivalent Identities in Study Abroad. (25th July 2017) - Anderson, Tim
Abstract: Intersections between transnationalism, the internationalization of higher education, and applied linguistics continue to draw attention, as the proliferation of academic mobility is increasingly influencing students, instructors, and universities globally. As one of the world's major receiving countries of international postsecondary students, Canada, and its universities, has been similarly impacted. This article presents two informative and contrastive perspectives based on the experiences of two Chinese doctoral students at a large Canadian university. I focus particularly on the students' national and transnational ideologies, identities, and future outlooks, and how these formative experiences and positionalities shaped their perspectives, goals, and motivations during their study abroad. This research demonstrates how the (transnational) identities of these two students were discursively and iteratively formed based on complex intersections of national and transnational discourses regarding the representations of overseas returnees and the students' conceptions and co-constructions of the legitimate academic transnational and home . These discursive constructions and enactments in turn had an influential effect on their challenges, desires, and abilities to integrate into local academic discourses and communities.